2023
DOI: 10.3390/buildings13030577
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on the Factors Affecting Bond Strength in Concrete

Abstract: The interaction of reinforcement bars with concrete determines the structural behavior and bond performance (bond strength) in reinforced cement concrete. Bond strength and its importance in structural applications based on available standards attracted researchers around the globe to evaluate the bond strength in reinforced cement concrete through various test methods and procedures. In this review article, more than 200 globally published studies were collected, and 170 articles were compiled to discuss the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 148 publications
0
2
0
Order By: Relevance
“…However, it is evident that the C f increased at the 10-mm diameter. Previous experiments have shown that rebars with larger diameters tend to trap more bleed water during concrete placement than those with smaller diameters, thus, lowering the bonding between concrete and steel (Chen and Su, 2021;Vembu and Ammasi, 2023). Bars with higher D o also have lower concrete confinement since they exhibit larger contraction under tensile stress (Xiao et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is evident that the C f increased at the 10-mm diameter. Previous experiments have shown that rebars with larger diameters tend to trap more bleed water during concrete placement than those with smaller diameters, thus, lowering the bonding between concrete and steel (Chen and Su, 2021;Vembu and Ammasi, 2023). Bars with higher D o also have lower concrete confinement since they exhibit larger contraction under tensile stress (Xiao et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Concrete with higher strength has a stronger bond between the paste and the aggregate, leading to improvements in the bond strength of concrete [51]. However, it is important to note that other factors such as the surface preparation and condition of the reinforcing bar can also affect the bond strength [52]. The enhancements in mechanical properties of concrete are found to substantially influence the bond performance between concrete and rebar [53].…”
Section: Bond Behavior Of Steel and Gfrp Rebars In Concretementioning
confidence: 99%